The role of self-congruity in the relationship between destination brand personality and revisit intention - Dede Kurnia; Agus Rahayu; Heny Hendrayati (Jurnal Manajemen dan Pemasaran Jasa, 2022)
The purpose of this study was to explore and analyze the direct influence of destination brand personality and the intermediary effect of self-congruity on the influence of destination brand personality on revisit intentions by including gender and emotional experience as moderator variables. This research were using a quantitative approach with an explanatory survey method. In this research,  we used a questionnaire as a data collection tool while determining the sample. It also used a non-probability sampling technique to obtain 100 visitors to the Sukahaji Waterboom Tourism Destination. It used Conditional Process Analysis (CPA) with the Regression approach and used Software Macro Process by Hayes as the data analysis technique. The goals of this paperindicate that destination brand personality has no direct effect on revisit intention. It shows that the effect of destination brand personality on revisit intention is transmitted by self-congruity. The results of the subsequent analysis show that emotional experience and gender do not moderate the effect of destination brand personality and self-congruity on revisit intention.